Flame-retardant antibacterial cellulose aerogel cross-linked with citric acid-mmt-il and preparation method thereof

CN120665343BActive Publication Date: 2026-10-27HUNAN UNIVERSITY SUZHOU INSTITUTE +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510833734.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2026-10-27
Estimated Expiration
2045-06-20

AI Technical Summary

Technical Problem

[0003]然而,纤维素本身的易燃等性质大大限制了其应用

Benefits of technology

1.本发明选用交联剂为柠檬酸,柠檬酸与CNF气凝胶的交联结构在湿润环境中保持稳定,且可以显著降低可燃气体(如CO)释放,提升CNF气凝胶的阻燃性能和水稳定性;交联结构也能提升气凝胶的力学性能,同时CA与纤维素的酯化反应能增强纤维素-MMT界面结合,使得材料力学性能进一步提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120665343B_ABST
    Figure CN120665343B_ABST
Patent Text Reader

Abstract

The application discloses a kind of flame-retardant antibacterial cellulose aerogel adopting citric acid-MMT-IL crosslinking and a preparation method thereof.CNF aerogel is treated by CA and MMT-IL for synergic modification, the rigid sheet layer of MMT can disperse stress and reduce local stress of the material, and the esterification reaction between CA and cellulose can enhance the interface bonding between cellulose-MMT, further improving the mechanical properties of the material; CA and MMT-IL can dilute combustible gas, capture free radicals and form a dense carbon layer to improve the flame-retardant properties of CNF aerogel; and the free ions in MMT-IL can endow CNF aerogel material with antibacterial properties and conductive properties, expanding the application field of CNF aerogel such as medical and intelligent device field, while the process is efficient and environmentally friendly, providing a new idea for green manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional fiber materials technology, specifically to a flame-retardant and antibacterial cellulose aerogel crosslinked with citric acid-MMT-IL and its preparation method. Background Technology

[0002] Nanocellulose, due to its unique structure, excellent properties, and processability, holds immense potential in manufacturing multifunctional foams or porous materials for various applications such as packaging, thermal insulation, sound absorption, flame retardancy, oil-water separation, energy storage and harvesting, filtration, and biomedicine. Furthermore, nanocellulose is a renewable, recyclable, and environmentally friendly natural material, easily obtained, aligning with current trends in sustainable development. Nanocellulose aerogels, produced using nanocellulose, are three-dimensional porous materials characterized by low density, high strength, high porosity, high specific surface area, low thermal conductivity, low thermal expansion, and sustainability. They can be applied in fields such as medicine, energy, environment, and construction.

[0003] However, the inherent flammability of cellulose significantly limits its applications. Therefore, improving flame retardancy is of paramount importance for further expanding the application areas of cellulose aerogels. Besides overcoming its flammability, it is also crucial to research and optimize other properties of cellulose aerogel materials to further broaden their application range. This includes improving the mechanical properties of aerogels, overcoming the cracking problem of large-size aerogels used in construction, optimizing their antibacterial or electrical properties for application in medical and smart devices, and simplifying the preparation process to explore green, economical, and continuous production methods to promote the industrialization of flame-retardant cellulose aerogels. Summary of the Invention

[0004] To address the above problems, this invention provides a flame-retardant and antibacterial cellulose aerogel crosslinked with citric acid-MMT-IL and its preparation method, thereby improving the flame retardancy, electrical conductivity, antibacterial properties and related mechanical properties of cellulose aerogel materials.

[0005] According to one objective of the present invention, the present invention provides a method for preparing a flame-retardant and antibacterial cellulose aerogel crosslinked with citric acid-MMT-IL, comprising the following steps: Step 1, Raw material extraction: The prepared natural fiber powder was alkali-hydrolyzed with an alkaline agent (70℃, 3h), then bleached with a bleaching agent (60-70℃, 1h), and finally acid-hydrolyzed with an acid hydrolysant to further purify the cellulose (4h). The resulting solution was then homogenized using a high-pressure homogenizer (3h) to obtain a uniformly dispersed nanofiber suspension. Step 2, Aerogel Molding: The homogenized cellulose nanofiber (CNF) dispersion obtained in step 1 was placed in an ultra-low temperature freezer for deep freezing pretreatment at -20°C, and then dried using a freeze dryer at a vacuum pressure range of 133 mbar to -133 mbar and a temperature of -54°C to obtain pure cellulose nanofiber (CNF) aerogel. Step 3, MMT-IL preparation: Montmorillonite (MMT) was dispersed in deionized water and stirred for 1 hour to allow its layered structure to fully expand. Ionic liquid was weighed according to the ratio and ultrasonically treated for 5 minutes to completely dissolve it in deionized water. The swollen MMT suspension was mixed with the ionic liquid solution and stirred at 60°C for 60 minutes to promote the insertion of cations (such as imidazolium) of the ionic liquid into the MMT interlayer through electrostatic interaction. Then, the mixture was centrifuged (10,000 rpm, 5 minutes) to remove unbound ionic liquid and dried at 80°C to obtain the MMT-IL nanocomposite material. Step 4, Crosslinking Modification: Pure CNF aerogel was immersed in a mixture of citric acid (CA), MMT-IL, 1 wt% catalyst, and 1 wt% dispersant for 24 hours. The immersed CNF aerogel was then dried at 130°C until fully cured using a high-temperature oven or curing furnace. After washing with deionized water to remove excess acid, it was dried a second time to obtain citric acid crosslinked cellulose aerogel material.

[0006] Preferably, the alkaline hydrolysant in step 1 is a 2wt% sodium hydroxide solution or potassium hydroxide solution, which is responsible for removing lignin and hemicellulose, swelling cellulose to loosen the fiber structure, and facilitating the subsequent separation of nanofibers.

[0007] Preferably, the bleaching agent in step 1 is a hydrogen peroxide solution or a peracetic acid solution, which is responsible for oxidizing residual lignin and pigments, improving cellulose purity, and sterilizing to ensure the stability of the raw materials.

[0008] Preferably, the acid hydrolysant in step 1 is a 12wt% citric acid solution, which further purifies cellulose in an acidic environment and promotes the separation of nanofibers.

[0009] Preferably, the ratio of ionic liquid in step 3 is 2:1 by weight of MMT to ionic liquid.

[0010] Preferably, the ionic liquid in step 3 is 1-methyl-3-octylimidazolium bromide, which generates imidazole cations and Br⁻ to form an ionic conductive network between the MMT layers, reducing the surface resistance of the material. Furthermore, the imidazole cations can enhance the antibacterial properties of the material by electrostatically adsorbing and destroying bacterial cell membranes. During the combustion of the aerogel, on the one hand, Br⁻ releases and captures highly reactive free radicals (such as H·, OH·), interrupting the chain combustion reaction. On the other hand, the imidazole cations promote the formation of a dense carbon layer during the pyrolysis of cellulose, further isolating heat.

[0011] Preferably, the citric acid concentration in step 4 is 16 wt%. The cross-linking structure of citric acid and CNF aerogel remains stable in a humid environment and can significantly reduce the release of combustible gases (such as CO), thereby improving the flame retardant properties and water stability of CNF aerogel. The cross-linking structure can also improve the mechanical properties of the aerogel. At the same time, the esterification reaction of CA and cellulose can enhance the bonding between the cellulose and MMT interfaces, thereby further improving the mechanical properties of the material.

[0012] Preferably, the weight concentration of MMT-IL in step 4 is 5 wt%. On the one hand, the silicate layer of MMT forms a dense carbon-silicate composite layer at high temperature, which acts as a barrier, reflecting heat radiation and isolating oxygen. On the other hand, MMT can enhance the melt viscosity of the material and reduce melt dripping. At the same time, the rigid sheets of MMT can disperse stress, reduce local stress concentration in the material, and improve the mechanical properties of the material.

[0013] Preferably, the catalyst in step 4 is one of disodium hydrogen phosphate, sodium dihydrogen phosphate, or trisodium phosphate. The phosphate ions dissociated from the catalyst in solution can provide an acidic environment for the cross-linking reaction, promote the protonation of cellulose hydroxyl groups (-OH) (forming R-OH2⁺), enhance their electrophilicity, and thus accelerate the esterification reaction between the carboxylic acid group (-COOH) of citric acid and the cellulose hydroxyl group to form a cross-linked structure.

[0014] Preferably, the dispersant in step 4 is polyvinylpyrrolidone (PVP), which is used to reduce the aggregation of MMT-IL in the aerogel material and improve dispersibility.

[0015] According to another objective of the present invention, the present invention provides a flame-retardant and antibacterial cellulose aerogel crosslinked with citric acid-MMT-IL prepared by the above method.

[0016] The beneficial effects of this invention are: 1. The present invention uses citric acid as the crosslinking agent. The crosslinking structure of citric acid and CNF aerogel remains stable in a humid environment and can significantly reduce the release of combustible gases (such as CO), thereby improving the flame retardant properties and water stability of CNF aerogel. The crosslinking structure can also improve the mechanical properties of the aerogel. At the same time, the esterification reaction of CA and cellulose can enhance the bonding between the cellulose-MMT interface, thereby further improving the mechanical properties of the material.

[0017] 2. The synergistic flame-retardant material selected in this invention is MMT-IL, which further enhances the flame-retardant and mechanical properties of aerogel materials, and also gives aerogel materials excellent electrical conductivity and antibacterial properties, expanding the application field of CNF aerogels. The ionic liquid 1-methyl-3-octylimidazolium bromide in MMT-IL can generate imidazole cations and Br⁻ to form an ionic conductive network between the MMT layers, reducing the surface resistance of the material. Furthermore, the imidazole cations can enhance the antibacterial properties of the material by electrostatically adsorbing and destroying bacterial cell membranes. During aerogel combustion, on the one hand, Br⁻ releases and captures highly reactive free radicals (such as H·, OH·), interrupting the chain combustion reaction; on the other hand, the imidazole cations promote the formation of a dense carbon layer during cellulose pyrolysis, further isolating heat. Meanwhile, the silicate layer of MMT forms a dense carbon-silicate composite layer at high temperatures, acting as a barrier, reflecting heat radiation and isolating oxygen; it also enhances the melt viscosity of the material, reducing melt dripping. The synergistic flame-retardant effect of these two elements significantly improves the flame-retardant performance of the material. Simultaneously, the rigid layers of MMT can disperse stress, reducing local stress concentration and improving the mechanical properties of the material.

[0018] 3. This invention uses montmorillonite (MMT) and the ionic liquid 1-methyl-3-octylimidazolium bromide to create a nanocomposite material through ion exchange. Compared with traditional brominated flame retardants, this material is more environmentally friendly, virtually non-volatile, has an extremely low release risk, and is multifunctional. Because the ionic liquid itself has an extremely low vapor pressure and is almost non-volatile, it reduces the risk of diffusion through the air. Its chemical structure is stable and does not easily decompose into free bromide ions or other harmful substances under normal use conditions. Simultaneously, it tightly binds with montmorillonite (MMT) through cation exchange to form a layered nanocomposite material. This structure effectively restricts the migration of bromide ions, reducing their release probability into the environment. Furthermore, this invention uses a lower actual dosage, resulting in less consumption.

[0019] 4. This invention uses one of disodium hydrogen phosphate, sodium dihydrogen phosphate, or trisodium phosphate as a catalyst for the cross-linking reaction. The phosphate ions dissociated from them in solution can provide an acidic environment for the cross-linking reaction, promote the protonation of cellulose hydroxyl groups (-OH) (forming R-OH2⁺), enhance their electrophilicity, thereby accelerating the esterification reaction between the carboxylic acid group (-COOH) of citric acid and the cellulose hydroxyl group to form a cross-linked structure.

[0020] 5. This invention optimizes the crosslinking modification process of CNF aerogel materials. Citric acid is both the crosslinking agent of this invention and the acid hydrolysate in the cellulose purification process. The MMT-IL nanocomposite material and the crosslinking agent are applied to the cellulose aerogel material simultaneously to achieve multifunctionality. This process avoids the traditional multi-step treatment (such as pretreatment → antibacterial treatment → flame retardant treatment → conductive coating, etc.), significantly simplifies the process and reduces resource consumption. It is both efficient and environmentally friendly, providing a new approach for green manufacturing. Attached Figure Description

[0021] Figure 1 This is a flowchart illustrating the preparation process of the citric acid crosslinked cellulose aerogel material of the present invention.

[0022] Figure 2 This is a schematic diagram illustrating the principle of MMT-IL modification. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention. Example

[0024] like Figure 1 and Figure 2 As shown, A method for preparing flame-retardant and antibacterial cellulose aerogel crosslinked with citric acid-MMT-IL includes the following steps: 1. Raw material extraction: The prepared natural fiber powder was alkali-hydrolyzed using an alkaline agent (70℃, 3h), then bleached using a bleaching agent (60-70℃, 1h), and finally hydrolyzed using an acid hydrolysant to further purify the cellulose (4h). The resulting solution was then homogenized using a high-pressure homogenizer (3h) to obtain a uniformly dispersed nanofiber suspension. In step 1, the alkaline agent was a 2wt% sodium hydroxide solution or potassium hydroxide solution; the bleaching agent was a hydrogen peroxide solution or peracetic acid solution; and the acid hydrolysant was a 12wt% citric acid solution.

[0025] 2. Aerogel molding: The homogenized CNF dispersion obtained in step 1 was placed in an ultra-low temperature freezer for deep freezing pretreatment at -20°C, and then dried using a freeze dryer at a vacuum pressure range of 133 mbar to -133 mbar and a temperature of -54°C to obtain pure CNF aerogel.

[0026] 3. Preparation of MMT-IL: Montmorillonite (MMT) was dispersed in deionized water and stirred for 1 hour to allow its layered structure to fully expand. Ionic liquid was weighed according to the specified ratio and sonicated for 5 minutes to completely dissolve in the deionized water. The swollen MMT suspension was mixed with the ionic liquid solution and stirred at 60°C for 60 minutes to encourage the cations of the ionic liquid (such as imidazolium) to embed into the MMT layers via electrostatic interaction. Then, centrifugation (10,000 rpm, 5 minutes) was performed to remove unbound ionic liquid, and the mixture was dried at 80°C to obtain the MMT-IL nanocomposite material. In step 3, the ionic liquid ratio was 2:1 (MMT to ionic liquid by weight); the ionic liquid was 1-methyl-3-octylimidazolium bromide.

[0027] 4. Crosslinking modification: Pure CNF aerogel was immersed in a mixture of citric acid (CA), MMT-IL, 1 wt% catalyst, and 1 wt% dispersant for 24 hours. The immersed CNF aerogel was then dried at 130°C until fully cured using a high-temperature oven or curing furnace. After washing with deionized water to remove excess acid, it was dried again to obtain the citric acid crosslinked cellulose aerogel material. In step 4, the citric acid concentration was 16 wt%; the MMT-IL concentration was 5 wt%; the catalyst was disodium hydrogen phosphate; and the dispersant was polyvinylpyrrolidone (PVP).

[0028] Comparative Example 2 The difference between this comparative example and Example 1 is that the weight concentration of MMT-IL in step 4 is 0 wt%.

[0029] Comparative Example 3 The difference between this comparative example and Example 1 is that the weight concentration of MMT-IL in step 4 is 2 wt%.

[0030] Comparative Example 4 The difference between this comparative example and Example 1 is that the citric acid concentration in step 4 is 12 wt% and the MMT-IL concentration is 0 wt%.

[0031] The flame retardant, electrical conductivity, antibacterial and mechanical properties of the prepared MMT-IL cross-linked cellulose aerogel material were tested.

[0032] As can be seen from Table 1, especially after adding MMT-IL to the mixture, the flame retardant properties of the aerogel material are significantly improved, and the LOI and residual carbon rate are greatly improved (about 30%). This is attributed to the formation of a dense carbon-silicate composite layer by the silicate layer of MMT at high temperature, which acts as a barrier, reflects heat radiation and isolates oxygen. Meanwhile, Br⁻ in MMT-IL releases and captures highly reactive free radicals (such as H·, OH·), interrupting the chain combustion reaction; imidazole cations promote the formation of a dense carbon layer during cellulose pyrolysis, further isolating heat.

[0033] Table 1 Comparison of Flame Retardant Performance Test Results

[0034] As can be seen from Tables 2, 3 and 4, after adding MMT-IL to the mixture, the surface resistance of CNF aerogel was significantly reduced, the conductivity was increased, and antibacterial properties were obtained. At the same time, the mechanical properties of the aerogel material were also greatly improved. This is because the ionic liquid 1-methyl-3-octylimidazolium bromide in MMT-IL can generate imidazole cations and Br⁻ to form an ionic conductive network between the MMT layers, reducing the surface resistance of the material. Furthermore, the imidazole cations can destroy bacterial cell membranes through electrostatic adsorption, thereby enhancing the antibacterial properties of the material. The rigid sheets of MMT can disperse stress, reduce local stress concentration, and improve the mechanical properties of the material. Meanwhile, the esterification reaction between CA and cellulose can enhance the bonding between the cellulose and MMT interfaces, thereby further improving the mechanical properties of the material.

[0035]

[0036] This invention aims to optimize the flame retardant and mechanical properties of nanocellulose aerogels, while also endowing them with certain antibacterial and electrical conductivity properties. CA and MMT-IL are selected for synergistic modification of CNF aerogels. The rigid sheets of MMT can disperse stress and reduce localized stress in the material. Simultaneously, the esterification reaction between CA and cellulose enhances the cellulose-MMT interfacial bonding, further improving the material's mechanical properties. CA and MMT-IL dilute flammable gases, capture free radicals, and form a dense carbon layer to improve the flame retardant properties of CNF aerogels. Furthermore, the free ions in MMT-IL can impart antibacterial and electrical conductivity properties to CNF aerogels, expanding their application areas to include medical and smart device fields. The process is both highly efficient and environmentally friendly, providing a new approach to green manufacturing.

[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing flame-retardant and antibacterial cellulose aerogel crosslinked with citric acid-MMT-IL, characterized in that, Includes the following steps: Step 1, Raw material extraction: Natural fiber powder was alkali-hydrolyzed at 70°C for 3 hours with an alkaline hydrolysant, then bleached at 60-70°C for 1 hour with a bleaching agent, and then further purified by acid hydrolysis for 4 hours with an acid hydrolysant. The resulting solution was homogenized by a high-pressure homogenizer for 3 hours to obtain a cellulose nanofiber dispersion. Step 2, Aerogel Molding: The homogenized cellulose nanofiber dispersion obtained in step 1 was pretreated by deep freezing at -20°C, and then freeze-dried under vacuum pressure of 133 mbar and temperature of -54°C to obtain pure cellulose nanofiber aerogel. Step 3, MMT-IL preparation: Montmorillonite was dispersed in deionized water and stirred for 1 hour to expand its layered structure. The ionic liquid, 1-methyl-3-octylimidazolium bromide, was weighed at a weight ratio of MMT to ionic liquid of 2:

1. The ionic liquid was ultrasonically treated for 5 minutes to dissolve it in deionized water. The swollen MMT suspension was mixed with the ionic liquid solution and stirred at 60°C for 60 minutes to allow the ionic liquid cations to embed into the MMT layers. Then, the unbound ionic liquid was removed by centrifugation at 10,000 rpm for 5 minutes and dried at 80°C to obtain the MMT-IL nanocomposite material. Step 4, Crosslinking Modification: Pure cellulose nanofiber aerogel was immersed in a mixture containing 16 wt% citric acid, 5 wt% MMT-IL, 1 wt% catalyst and 1 wt% dispersant for 24 hours, dried at 130°C until completely cured, washed with deionized water to remove excess acid and dried a second time to obtain citric acid crosslinked cellulose aerogel material.

2. The preparation method according to claim 1, characterized in that, The alkaline hydrolysant in step 1 is a 2wt% sodium hydroxide solution or potassium hydroxide solution.

3. The preparation method according to claim 1, characterized in that, The bleaching agent in step 1 is a hydrogen peroxide solution or a peracetic acid solution.

4. The preparation method according to claim 1, characterized in that, The acid hydrolysate in step 1 is a 12wt% citric acid solution.

5. The preparation method according to claim 1, characterized in that, The catalyst in step 4 is one of disodium hydrogen phosphate, sodium dihydrogen phosphate, or trisodium phosphate.

6. The preparation method according to claim 1, characterized in that, The dispersant in step 4 is polyvinylpyrrolidone.

7. A flame-retardant and antibacterial cellulose aerogel crosslinked with citric acid-MMT-IL, prepared by the method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Preparation method of citric acid cross-linking reinforced cellulose aerogel

    CN105542218A

  • Dual-drying degradable nanocellulose composite antibacterial aerogel as well as preparation method and application thereof

    CN115558152A